The Effect of Financing Trading, Profit Sharing and Ijarah to Falah in Sharia Banks - Imam Mas’ud; Eko Setiawan; Norita Citra Yuliarti (Journal of Contemporary Information Technology, Management, and Accounting, 2020)
Each industry or individual cannot be separated from the need for funding to finance the industry or carry out consumption. Financing can be very crucial because this financing factor is as the key of development of Islamic business in the future. Ideally, Islamic Bank financing is dominated by the principle of purchase and sales financing, the principle of profit-sharing financing and the principle of ijarah financing where those financing is held using bargaining agreements and profit-sharing which must be agreed by sharia principle. This research examines the effect of information content on the principle of purchase and sales financing, the principle of profit-sharing financing and the principle of ijarah financing to falah of Islamic bank (BUS). This sample uses purposive sampling method in BUS that exists and releasing financial statements between 2011 and 2016 in which they are not loss. Data is collected from Bank Indonesia and the BUS website's. The result of this research using Structural Equation Modeling (SEM) shows that two variables which are the principle of purchase and sales financing and the principle of profit-sharing financing have positive significantly affect to falah in Islamic bank.